(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
This thesis examines the terminology of external debt, theoretical aspects of external debt, methods of external debt regulation, examples of countries by methods of external debt regulation. During the study, an analysis of the dynamics of external debt of foreign countries, its structure and creditors and the distribution of external debt by industry were carried out. The thesis also examines the reasons for the increase in public debt and develops strategies for further reduction of public external debt.